A comprehensive review of the health perspectives of resveratrol. Issue 12 (18th October 2017) - Rauf, Abdur; Imran, Muhammad; Suleria, Hafiz Ansar Rasul; Ahmad, Bashir; Peters, Dennis G.; Mubarak, Mohammad S.
Abstract : Graphical abstract showing the structure of resveratrol. Abstract : Many natural products present in our diet, including flavonoids, can prevent the progression of cancer and other diseases. Resveratrol, a natural polyphenol present in various fruits and vegetables, plays an important role as a therapeutic and chemopreventive agent used in the treatment of various illnesses. It exhibits effects against different types of cancer through different pathways. It additionally exerts antidiabetic, anti-inflammatory, and anti-oxidant effects in a variety of cell types. Furthermore, the cardiovascular protective capacities of resveratrol are associated with multiple molecular targets and may lead to the development of novel therapeutic strategies for atherosclerosis, ischemia/reperfusion, metabolic syndrome, and heart failure. Accordingly, this article presents an overview of recent developments in the use of resveratrol for the prevention and treatment of different diseases along with various mechanisms. In addition, the present review summarizes the most recent literature pertaining to resveratrol as a chemotherapeutic agent against multiple diseases and provides an assessment of the potential of this natural compound as a complementary or alternative medicine.